2018
DOI: 10.1093/nar/gky1057
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and structure of flanking DNA impact transcription factor affinity for its core motif

Abstract: Spatial and temporal expression of genes is essential for maintaining phenotype integrity. Transcription factors (TFs) modulate expression patterns by binding to specific DNA sequences in the genome. Along with the core binding motif, the flanking sequence context can play a role in DNA–TF recognition. Here, we employ high-throughput in vitro and in silico analyses to understand the influence of sequences flanking the cognate sites in binding of three most prevalent eukaryotic TF families (zinc finger, homeodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 70 publications
4
67
1
Order By: Relevance
“…6 Our data allows differentiating between high and low affinity response elements flanking sequences. In accordance with a recent HT-SELLEX and bioinformatics study 19 focusing on the BZIP factors Fos-Jun and NFIL3, we show that the flanking 5'-GA step promotes stable selective DNA-Yap1 binding. The flanking 5'-TA step, which is listed as high affinity for the NFIL3 factor, is less favourable for Yap1; thus, indicating that at least two adjacent flanking nucleotides that surrounds the response element can modulate the selectivity among different BZIP factors.…”
Section: Impact Of Dna Flanking Environmentsupporting
confidence: 90%
See 1 more Smart Citation
“…6 Our data allows differentiating between high and low affinity response elements flanking sequences. In accordance with a recent HT-SELLEX and bioinformatics study 19 focusing on the BZIP factors Fos-Jun and NFIL3, we show that the flanking 5'-GA step promotes stable selective DNA-Yap1 binding. The flanking 5'-TA step, which is listed as high affinity for the NFIL3 factor, is less favourable for Yap1; thus, indicating that at least two adjacent flanking nucleotides that surrounds the response element can modulate the selectivity among different BZIP factors.…”
Section: Impact Of Dna Flanking Environmentsupporting
confidence: 90%
“…17 The high-throughput study by Steger and colleagues 18 focusing on another subfamily of BZIPs, CREBP transcription factors, showed a strong preference for 5'-R and 3'-Y flanking nucleotides, directly adjacent to the response elements. Bansal and colleagues 19 further highlighted the importance of the flanking regions for several transcription factors, including the BZIP proteins Fos-Jun (which prefer 5'-RR and 3'-YY-flanks) and NFIL3 (which prefer YR for both 5'-and 3'-flanks). Both studies proposed that DNA shape readout could contribute to BZIP-proteins binding specificity, since only nonspecific contacts with the DNA backbone of the flanking nucleotides were found in the crystal structures of the BZIP-DNA complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Segment [15] also suppresses a characterized TFBS for a different TF, En, and results in higher activity in the posterior wing compartment, also consistent with previous work (Gompel et al, 2005) ( Figure 1B). Likewise, mutations can influence TF binding at neighboring TFBSs, as TF affinity can be affected by the nature of sequences around the TFBS (Gordan et al, 2013;Slattery et al, 2014;Yella et al, 2018), particularly by altering DNA shape properties Hizver et al, 2001;Yella et al, 2018). A-tract mutations may also influence nucleosome occupancy and positioning and thereby the binding of TFs at adjacent sites (Barozzi et al, 2014).…”
Section: Every Nucleotide Position Along the Spot 196 Enhancer Contrimentioning
confidence: 99%
“…Various studies have shown that the flanking regions outside of the core binding sites affect TF binding, by affecting DNA shape preferences or by harboring binding sites of co-cooperatively binding TFs at variable spacings [14,[45][46][47]. Therefore, we investigated the impact of extending the core motifs, by adding two or four nucleotides on each side in the seeding motifs and refining the extended motifs with BaMMmotif2.…”
Section: Extended Flanking Regions Increase Motif Prediction Accuracymentioning
confidence: 99%